Skeletal muscle inflammation following repeated bouts of lengthening contractions in humans - Deyhle, Michael R.; Gier, Amanda M.; Evens, Kaitlyn C.; Eggett, Dennis L.; Nelson, W. B.; Parcell, Allen C.; Hyldahl, Robert D. (Frontiers in Physiology, 2016)
Skeletal muscle responds to exercise-induced damage by orchestrating an adaptive process that protects the muscle from damage by subsequent bouts of exercise, a phenomenon called the repeated bout effect (RBE). The mechanisms underlying the RBE are not understood. We hypothesized that an attenuated inflammation response following a repeated bout of lengthening contractions (LC) would be coincidental with a RBE, suggesting a potential relationship. Fourteen men (n=7) and women (n=7) completed 2 bouts of lengthening contractions (LC) separated by 28 days. Muscle biopsies were taken before the first bout (B1) from the non-exercised leg, and from the exercised leg 2- and 27-d post-B1 and 2-d following the second bout (B2). A 29-plex cytokine array identified alterations in inflammatory cytokines. Immunohistochemistry quantified inflammatory cell infiltration and major histocompatibility complex class 1 (MHC-1). Muscle soreness was attenuated in the days following B2 relative to B1, indicating a RBE. Intramuscular monocyte chemoattractant protein (MCP1) and interferon gamma-induced protein 10 (IP10) increased following B2 relative to the pre-exercise sample (7 pg/ml to 52 pg/ml, and 11 pg/ml to 36 pg/ml, respectively p<0.05). Interleukin 4 (IL4) decreased (26 pg/ml to 13 pg/ml, p<0.05) following B2 relative to the pre-exercise sample. Infiltration of CD68+ macrophages and CD8+ T-cells were evident following B2, but not B1. Moreover, CD8+ T-cells were observed infiltrating apparently necrotic muscle fibers. No changes in MHC-1 were found. We conclude that inflammation is not attenuated following a repeated bout of LC and that CD8+ T-cells may play a role in muscle adaptation following LC. Moreover, it appears that the muscle or the immune system becomes sensitized to an initial bout of damaging exercise such that inflammatory cell infiltration into the muscle is enhanced upon a repeated bout of damaging exercise.